SERUM INSULIN AND CRP AS PREDICTORS OF GLYCEMIC CONTROL IN TYPE 2 DIABETIC PATIENTS - Arvind Kumar Gupta; Dr. Nikhil Rajak; Dr. Anurag Kesarwani; Simran Bamniya; Raashika Saxena (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is a complex metabolic disorder characterized by insulin resistance and chronic low-grade inflammation. In India alone, over 72 million individuals currently live with diabetes, and this number is projected to nearly double by 2045.Objectives: In this study, we aimed to investigate the correlation between serum insulin and CRP levels with HbA1c in T2DM patients to assess their predictive value in determining glycemic control.Materials and Methods: A hospital-based cross-sectional observational study included on 100 T2DM patients aged 20-65 years. Fasting serum insulin and CRP levels were measured and correlated with glycemic status.Results: The results showed that poor glycemic control was significantly associated with elevated CRP and fasting insulin levels.Conclusion: These findings suggest that insulin resistance and inflammation play pivotal roles in the pathophysiology of T2DM and that CRP and insulin may serve as useful biomarkers in predicting glycemic control.